2023
DOI: 10.1021/acs.estlett.3c00499
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Induced Transformation of Tire Rubber Antioxidant N-(1,3-Dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD) to 6PPD-Quinone in Water

Yangjian Zhou,
Lacuo Yixi,
Qingqing Kong
et al.

Abstract: The huge consumption of the tire rubber antioxidant N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD) has resulted in pervasive contamination in aquatic environments. More importantly, the transformation product of 6PPD, i.e., 6PPD-quinone (6PPD-Q), is raising increasing concerns due to its high toxicity to aquatic organisms. However, whether and how 6PPD-Q can be formed from 6PPD in aquatic environments remain unknown. Herein, we reported the transformation of 6PPD to 6PPD-Q in water under sunlight ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…23 The concentrations of 6PPD were much higher than those reported elsewhere, e.g., 300− 14 300 ng/L in a German wastewater treatment plant 26 and 21−130 ng/L in road runoff from Pierce County (USA). 27 According to Zhou et al, 28 the presence of organic matter and sunlight may enhance the formation of 6PPD-Q in a continuous manner. Hence, the high levels of 6PPD in the discharged tunnel wash water are concerning.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…23 The concentrations of 6PPD were much higher than those reported elsewhere, e.g., 300− 14 300 ng/L in a German wastewater treatment plant 26 and 21−130 ng/L in road runoff from Pierce County (USA). 27 According to Zhou et al, 28 the presence of organic matter and sunlight may enhance the formation of 6PPD-Q in a continuous manner. Hence, the high levels of 6PPD in the discharged tunnel wash water are concerning.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A Q-SUN Xe-1 sunlight simulator equipped with an 1800 W xenon lamp and an optical filter with a 315 nm cutoff was used for the irradiation experiments. The total absolute irradiance spectrum of the sunlight simulator was measured using an Ocean Optics USB-4000 spectrometer with results shown in Figure S2c. , The intensity of the simulated sunlight irradiation in the range of 315–600 nm was determined to be 5.89 × 10 –5 Einstein·L –1 ·s –1 by p -nitroanisole/pyridine (Figure S4). …”
Section: Methodsmentioning
confidence: 99%
“…The total absolute irradiance spectrum of the sunlight simulator was measured using an Ocean Optics USB-4000 spectrometer with results shown in Figure S2c. 16,23 The intensity of the simulated sunlight irradiation in the range of 315−600 nm was determined to be 5.89 × 10 −5 Einstein•L −1 • s −1 by p-nitroanisole/pyridine (Figure S4). 24 Eighteen milliliters of solution containing 10 μM of each deoxynucleoside and 5.0 mg C •L −1 of EfOM or SRNOM was irradiated in a capped quartz container under simulated solar irradiation from the top xenon lamp (Figure S3).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…14,18 Recently, a few studies have elucidated the underlying phototransformation mechanisms of several OPAs and 6PPD through in-lab simulation. 65,66 However, the transformation products of most synthetic antioxidants have not been explored, which requires further study. Identifying novel contaminants from secondary sources (transformation products) in indoor dust is a significant challenge due to chemical and matrix complexity.…”
Section: Knowledge Gaps Of Synthetic Antioxidants and The Pathways Fo...mentioning
confidence: 99%
“…Previous studies have demonstrated that indoor dust contains only low concentrations of AO168. By contrast, very high concentrations of tris­(2,4-di- tert -butylphenyl) phosphate (AO168O), which is the oxidation product of AO168, have been observed in indoor dust. , The transformation products of synthetic antioxidants can be more toxic than their corresponding parent chemicals, particularly quinones such as BHT-Q and 6PPD-Q (derived from BHT and 6PPD, respectively). , Recently, a few studies have elucidated the underlying phototransformation mechanisms of several OPAs and 6PPD through in-lab simulation. , However, the transformation products of most synthetic antioxidants have not been explored, which requires further study. Identifying novel contaminants from secondary sources (transformation products) in indoor dust is a significant challenge due to chemical and matrix complexity.…”
Section: Knowledge Gaps Of Synthetic Antioxidants and The Pathways Fo...mentioning
confidence: 99%